Proceedings of the 2015 Asia International Conference on Quantitative InfraRed Thermography 2015
DOI: 10.21611/qirt.2015.0018
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography applied to surface temperature survey of enhanced pavement sample addressing self-de-icing functionality

Abstract: The mobility during winter season in France mainly relies on the use of de-icers, with an amount ranging from two hundreds thousands tons up to two millions tons for the roads only. Besides the economic impact, there are many concerns on their environmental and infrastructure, both on roads and on airports. In such context and in the framework of the R5G (5th Generation Road) project driven by IFSTTAR, investigations were carried out on the way to modify the infrastructure to maintain pavement surface at a tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Still the amounts of de-icers are increasing, conducting to consider a modification of the infrastructure itself to make it compliant with the avoidance of ice occurrence and snow accumulation, as performed on the Serso bridge in Switzerland [7]. Previous research indicated the benefits of a multilayered asphalt concrete [8] and phase change materials (PCM) included into a pavement [9]. These inclusions are meant to maintain a constant surface temperature during the phase transition process.…”
Section: Introductionmentioning
confidence: 99%
“…Still the amounts of de-icers are increasing, conducting to consider a modification of the infrastructure itself to make it compliant with the avoidance of ice occurrence and snow accumulation, as performed on the Serso bridge in Switzerland [7]. Previous research indicated the benefits of a multilayered asphalt concrete [8] and phase change materials (PCM) included into a pavement [9]. These inclusions are meant to maintain a constant surface temperature during the phase transition process.…”
Section: Introductionmentioning
confidence: 99%
“…Such solution has nevertheless to be compliant with maintenance and repairs works on pavements, and is in full opposition and contrast with such changes as ones made on Serso Bridge (Switzerland) for instance. Previous works consisted in evaluation the performance of a multi-layered asphalt concrete structure with a fluid circulating a porous layer, and of phase change materials (PCM) embedded into concrete [6]. Additional tests were then conducted considering another phase change material [7] with the appropriate thermodynamic characteristics in the form of inclusions into asphalt concrete, and submitted to controlled winter conditions during several days.…”
Section: Introductionmentioning
confidence: 99%